Improvements to a smooth particle hydrodynamics simulator for investigating submarine landslide generated waves - Snelling,BE; Collins,GS; Piggott,MD; Neethling,SJ (International Journal for Numerical Methods in Fluids, 2020)
Submarine landslides can exhibit complex rheologies, including a finite yield stress and shear thinning, yet are often simulated numerically using a Newtonian fluid rheology and simplistic boundary conditions. Here we present improvements made to a Smoothed Particle Hydrodynamics simulator to allow the accurate simulation of submarine landslide generated waves. The improvements include the addition of Bingham and HerschelBulkley rheologies, which better simulate the behavior of submarine mudflows. The interaction between the base of the slide and the slope is represented more accurately through the use of a viscous stress boundary condition. This condition treats the interface between the seafloor and the slide as a fluid boundary layer with a userdefined viscosity and length scale. Modifications to the pressure and density calculations are described that improve their stability for landslide generated wave scenarios. An option for pressure decomposition is introduced to prevent particle locking under high pressure. This facilitates the application of this simulator to landslide scenarios beneath significant water depths. Additional modifications to the reaveraging and renormalization routines improve the stability of the free surface and fluid density. We present the mathematical formulations of these improvements alongside commentary on their performance and applicability to landslide generated wave modeling. The modifications are verified against analytical fluid flow solutions and a wave generation experiment.